2014
DOI: 10.5935/1518-0557.20140012
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian as predictor of reproductive outcome in infertile women: follow up

Abstract: Objective: The aim of the present study was to investigate and to compare the relations of anti-Mullerian with the prognostic parameters and the outcome of assisted reproductive treatment. Methods: Prospective longitudinal study. A total of one hundred and twelve infertile women. Inclusion criteria: i) both ovaries present, ii) no current or past diseases affecting ovaries or gonadotropin or sex steroid secretion, clearance, or excretion, iii) no current hormone therapy, iv) adequate visualization of ovaries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Our study showed a significant difference in the mean AMH concentration in both fertile and infertile women. Our study was consistent with Broer et al suggestion that AMH could be used to predict response during ovulation and the reproductive process, whereas some studies reported on AMH and antral follicle count (AFC) (Han et al, 2022;Iuliano et al, 2022;Lan et al, 2013;Muharam et al, 2022;Mutlu et al, 2013;Scheffer et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed a significant difference in the mean AMH concentration in both fertile and infertile women. Our study was consistent with Broer et al suggestion that AMH could be used to predict response during ovulation and the reproductive process, whereas some studies reported on AMH and antral follicle count (AFC) (Han et al, 2022;Iuliano et al, 2022;Lan et al, 2013;Muharam et al, 2022;Mutlu et al, 2013;Scheffer et al, 2014).…”
Section: Discussionsupporting
confidence: 91%